Optimizing the Use of Differentiated Instruction Strategies to Accommodate Diverse Student Needs - Meriyati, Meriyati; Sumianto, Sumianto; Nusraningrum, Dewi; Cheriani, Cheriani; Guilin, Xie; Jiao, Deng (Journal International Inspire Education Technology, 2023)
Education at school is very important for a student to develop the potential he has. To maximize this potential, a strategy is needed that suits the needs of each student. Teachers are required to recognize and understand the various characteristics of students, in order to maximize the strategies needed by students. For this reason, the use of the Differented Instruction strategy is utilized to accommodate the diverse needs of these students. The Differented Instruction strategy is a method used to adapt the various characteristics of students to learning and assessment, which does not only use one strategy but combines several suitable strategies. The purpose of this research is to find out that optimizing the use of Differentiated Instruction strategies is very beneficial for the diverse needs of students. By maximizing this strategy can have a major positive impact on the development of student education. As proficient they optimize their abilities to be more productive and creative. The method used in this research is a quantitative research method. The data obtained is through the distribution of a questionnaire. The questionnaire was made using the Google form application. The results of this study explain that optimizing the use of Differentiated Instruction strategies to accommodate the diverse needs of students in order to maximize their own potential, understand how to do assignments in a fun way, and be able to learn according to the needs of each student with a variety of backgrounds. So that the various knowledge given by the teacher can be absorbed optimally. The conclusion from this study is that optimizing the use of Differentiated Instruction strategies to accommodate student needs is very effectively used in learning. The limitation of this research is that researchers only conduct this research at the school/madrasah level which incidentally requires a new strategy in learning such as the use of this Differentiated Instruction strategy.